Stakeholder views on shifting UK chicken meat production to slower-growing broilers - Abeyesinghe, Siobhan M.; Stanley, Imogen; Nicol, Christine J.; Cardwell, Jacqueline M. (Frontiers in Animal Science, 2025)
IntroductionLongstanding concerns about the welfare of conventional broiler chickens used to produce chicken meat have led to commitments by 104 UK retailers, restaurants, and food service providers, that by 2026 their poultry products will meet the ‘‘Better Chicken Commitment’’ (BCC) requirements, including production using slower-growing strains that demonstrate better welfare outcomes. However, a wide-scale transition to production using these strains has not occurred in the UK. MethodsTo explore the reasons underpinning this limited movement and potential solutions, qualitative content analysis of data from 30 semi-structured interviews with representatives of the UK poultry industry, retailers, assurance schemes, animal welfare organisations, and animal welfare scientists was conducted. ResultsKey barriers identified were increased economic and environmental costs of production using slower-growing strains, which would produce less meat per unit area, coupled with uncertainties about consumer appetite and willingness to pay for these welfare improvements. Stakeholders differed in their focus. Retailer and industry representatives emphasised meeting current consumer demand, provision of affordable food, and minimising carbon footprint in alignment with legislated commitments and UK government priorities. Animal welfare organisations, assurance schemes, and scientists viewed sustainability more holistically. They highlighted the need for transformative change in the food system and consumer behaviour for a sustainable future encompassing improvements in broiler welfare. Suggested solutions included ways to minimise economic and environmental costs, better alignment of consumer purchasing with preferences through improved clarity in labelling and marketing, and alternative strategies for improving broiler welfare. However, stakeholders diverged on the perceived feasibility, relevance, and effectiveness of these solutions. DiscussionInsufficient relevant and comprehensive data on economic, environmental, and social elements of sustainability, integrating animal welfare, currently compromise decision-making on the best way forward. If UK broiler welfare improvements are to be market-driven, robust contextually relevant evidence is needed to evaluate these trade-offs for all strategies and risk mitigations, to achieve welfare improvement whilst balancing sustainability goals.